Secrets of mlearning failures: confronting reality - Thomas Cochrane (Association for Learning Technology, 2012)
Having implemented and evaluated over 35 mlearning projects in a variety of contexts in higher education over the past 6 years the researcher is ready to share the untold secret: not all mlearning projects succeed! This article critiques three of the researcher's mlearning projects that can be classed as “failures” and compares them to successful projects to draw out critical implications for mlearning project design and implementation to avoid common pitfalls leading to potential project failure. This article uses the researcher's six critical success factors identified across the 35 mlearning projects to evaluate these three projects, and concludes that projects resulting in “no significant difference” in pedagogical outcomes are the result of attempts to shoehorn old pedagogies into new technologies. Lecturer professional development and sustained collaborative support are critical to fostering new pedagogies utilising the unique affordances of mobile devices.